Outpatient Sistrunk procedure: A retrospective analysis. (December 2020) - Pool, Christopher; Rosi-Schumacher, Mattie; Ehret, Christopher; King, Tonya S.; Wilson, Meghan N
Abstract: Objective: The risk of expansile hematoma and airway compromise following neck surgery have been used to validate overnight observation. We investigated the outcomes of pediatric patients undergoing a Sistrunk procedure via either same day surgery or overnight observation. Methods: A retrospective review of patients undergoing Sistrunk procedures between January 1, 2008 to January 1, 2019 was performed. 76 cases were identified for review. Bivariate and multivariable analyses were performed to determine predictive factors for overnight admission as well as associations between overnight observation and adverse outcomes (hematoma, seroma, airway compromise, infection). Factors evaluated for analysis included ASA class, surgeon type, history of pre-operative infection, recurrent case, operation >90 min, pharyngeal violation, intraoperative cyst rupture, cyst size, and drain placement. Results: No patients had life-threatening adverse events. There was no difference in complication rates between same day discharge (17%) and overnight observation (23%, p = 0.47). Otolaryngologists were more likely to admit patients overnight (88% vs. 14%, p = 0.042) as well as place a drain (97% vs. 24%, p < 0.001) when compared to pediatric surgeons. Drain placement was associated with overnight observation (73% vs. 3%, p < 0.001). Multivariable logistic regression demonstrated drain placement (OR 21.9, 95%CI (2.5–189.7), p = 0.005) and otolaryngologist as operative surgeon (OR 11.7, 95%CI (2.8–48.2), p < 0.001) as strong predictive variables for overnight observation. There was no association between other investigated variables and adverse events or overnight stay. Conclusion: Same day Sistrunk operations are safe in select healthy patients. Overnight observation appears to be driven by drain placement and surgeon practice patterns.